A, The An Overview of Serum Amyloid A in Obstetrical Complications: Amyloid A in Obstetrics - ali, Alaa; nori, wassan; Hamed, Roaa (Karbala Journal of Medicine, 2021)
Serum Amyloid A (SAA) has remained a mystery since its discovery. Its remarkable evolutionary biodiversity and dynamic synthesis control have always held a powerful position in biology. It belongs to a family of apolipoproteins produced in response to cytokines released by activated monocytes and macrophages, isolated in the last 50 years. The lipophilicity of SAA spotlight its relation to lipid transport and metabolism. Evidence supported its role in the acute phase response, orchestrating inflammation, immunological reactions and trauma. SAA initiates many physiological reactions, such as fever, metabolic changes, and hormonal changes. SAA's participation in acute inflammatory response physiology has encouraged its use as a marker for the inflammatory process in obstetrical diseases. This review emphasizes human SAA protein as a sensitive biochemical marker for several common pregnancy complications.